(untitled) (Baghdad Science Journal, 2021)
Leishmaniasis is a group of parasitic diseases caused by Leishmania spp., an endemic infectious agent in developing countries, including Iraq. Diagnosis of cutaneous lesion by stained smears, serology or histopathology are inaccurate and unable to detect the species of Leishmania. Here, two molecular typing methods were examined to identify the promastigotes of suspected cutaneous leishmaniasis samples, on a species level. The first was species-specific B6-PCR and the second was ITS1-PCR followed by restriction fragment length polymorphism (RFLP) using restriction enzyme HaeIII. DNA was extracted from in vitro promastigote culture followed by amplification of kDNA by B6 or amplification and digestion of LITSR/L5.8S. PCR produced bands of 359 bp and 450 bp for B6 and ITS1, respectively. Digestion of ITS1 by RFLP revealed two distinct bands of 150 bp and 300 bp size. The results reviled that the two isolates belong to cutaneous Leishmaniasis, specifically Leishmania tropica. In conclusion, the confirmation of the studied methods will improve rapid and accurate diagnosis of Leishmania species of the most prevalent Iraqi strain of cutaneous leishmaniasis, L. tropica.